A construção de vínculos religiosos na cibercultura: a ciber-religião - Miklos, Jorge (2010)
This research aims to compromise the phenomenon in the religious media and the mediatic religion in the conjuncture of the cyber-religion. The researched feature is to understand the religious media and the mediatization of the religion from the context of modernity and the usurpation through the religious media, specially the means of interactive and the electronic means of communication (most computers and other technologies that use the net) of the divine power and the religious and mediatic religions in the net religious experiences. The main problem in the research is set between two categories: the mediatic and the religious. The question that has motivated the research was: what changes religions have when they start their cyberspace virtual environment. The first hypothesis concentrates on the idea that there is a double contamination between religion and media, that is, the mediatic formats get the religious elements and religions use the media for their own benefits. There is a mutual interpenetration: religion gets into the media and simultaneously the media is sacralized. Thus, we observe two phenomena: the first one is that the interactive electronic means of communications get all the divine elements (the media sacralizes itself) and the religion mediates itself; the second testified phenomenon is that the religious experiences in the cyber-space (the cyber-religion) has the phenomenon of body abolition and space invalidation, two essential features not only for the religious experience but also for the communication events. The area of investigation is the Communication Science, a productive area for the interlacement of epistemological and different looks. On account of the hybrid nature of analysis objects, the theorical reference of the research uses, as a conceptual foundation, the theorical help planned by the Semiotics of Culture by professor Ivan Bystrina, Media Theory of Harry Pross and Vilém Flusser, in the formulation of communication concept for the cultural structure of symbolic texts as from the reading of processes of communication bonds by Norval Baitello Junior, the mediosfera studies, and its place in the mediatic religious imagination by Malena Segura Contrera. For the understanding of the religious phenomenon one should go to the delineated concepts by Mircea Eliade and Joseph Campbell. The research is also supported by works of cyber-culture theorists like Paul Virilio and Eugenio Trivinho, as well as in contemporaneity studious people, in areas linked to communication, such as Zygmunt Bauman and David Harvey. The concepts of sacred and profane space and time, religare, cyberculture, cyberspace, democracy, glocal, and compression of space and time are necessary for the understanding of the advent of religious experiences adapted to the cyberspace. The corpus of analysis referring to this feature has come through some communication practices that are in the virtual environments that allow religious experiences such as the constitution of new cyber-rituals as the virtual candles, virtual wakes, virtual beads and virtual pilgrimages